2020
DOI: 10.3390/sym12061015
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotizability-Related Asymmetries: A Review

Abstract: Hypnotizability is a dispositional trait reflecting the individual ability to modify perception, memory and behavior according to imaginative suggestions. It is measured by validated scales that classify the general population in high (highs), medium (mediums) and low (lows) hypnotizable persons, predicts the individual proneness to respond to suggestions, and is particularly popular in the field of the cognitive control of pain and anxiety. Different hypnotizability levels, however, have been associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 148 publications
2
9
1
Order By: Relevance
“…This combination tends to be observed in each of his sessions. The maps of the other patients demonstrate some similar changes: the slow-wave activity increase in different areas of their brain, which corresponds to the literature on the electrophysiological correlates of hypnosis (Cordi et al, 2014; De Benedittis, 2021; Deivanayagi et al, 2007; De Pascalis et al, 1998; De Pascalis & Santarcangelo, 2020; Freeman et al, 2000; Jamieson & Burgess, 2014; Jensen et al, 2015, 2018; Kropotov, 2009; Paoletti et al, 2020; Sabourin et al, 1990; Vaitl et al, 2005; Wolf et al, 2022). Nevertheless, they also show quite clear differences between patients.…”
Section: Discussionsupporting
confidence: 86%
“…This combination tends to be observed in each of his sessions. The maps of the other patients demonstrate some similar changes: the slow-wave activity increase in different areas of their brain, which corresponds to the literature on the electrophysiological correlates of hypnosis (Cordi et al, 2014; De Benedittis, 2021; Deivanayagi et al, 2007; De Pascalis et al, 1998; De Pascalis & Santarcangelo, 2020; Freeman et al, 2000; Jamieson & Burgess, 2014; Jensen et al, 2015, 2018; Kropotov, 2009; Paoletti et al, 2020; Sabourin et al, 1990; Vaitl et al, 2005; Wolf et al, 2022). Nevertheless, they also show quite clear differences between patients.…”
Section: Discussionsupporting
confidence: 86%
“…In the frequency domain, we limited our investigation to theta, alpha and gamma PSD. Theta and alpha are, in fact, the EEG frequency bands most studied during relaxation and hypnosis, although inconsistent findings of their hypnotizability-related and hypnosis-induced difference have been reported [9,47], and high gamma activity has been To support the relevance of the hypnotizability trait in the mRP differences across the session, we correlated the values of DET and ENT observed during hypnosis with those found during closed-eyes relaxation, which is the condition most similar to NH except for hypnotic induction. We observed, in fact, a significant positive correlation between R CE and NH (DET, ρ = 0.646, p = 0.0001; ENT, ρ = 0.910, p = 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the limpia , particularly during the initial preparation, alpha activity involving resting and relaxed but attentive states of wakefulness was observed ( Sanei and Chambers, 2007 ). Some authors have suggested that alpha activity is the first EEG element affected by preparation for a non-ordinary state of consciousness – for example, in hypnosis or in transcendental meditation that elicits a sensation of completeness in practitioners with several years of experience ( De Pascalis and Santarcangelo, 2020 ; Callara et al, 2023 ). This alpha state would suggest that practice and training configure a state of consciousness similar to the transition to stage 1 sleep, with certain similarly hypnagogic effects ( Lyubimov, 1999 ; Hankey, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transcendental meditation is associated with brain activity that oscillates between alpha and beta waves ( Lyubimov, 1999 ). Hypnosis has been associated with theta and alpha frequencies, although gamma activity is particularly recurrent in people with high hypnotizability ( De Pascalis and Santarcangelo, 2020 ; Callara et al, 2023 ); in Tibetan Buddhist monks, an increase in gamma frequencies has been reported during compassion meditation ( Lutz et al, 2004 ). Other neuroimaging techniques have been used in some reports.…”
Section: Introductionmentioning
confidence: 99%